Cutaneous ulcers following hydroxyurea therapy - Hartmann, K.; Nagel, S.; Erichsen, T.; Rabe, E.; Grips, K. H.; Bieber, T.; Pannier-Fischer, F. (Phlebologie, 2004)
Hydroxyurea (HU) is usually a well tolerated antineoplastic agent and is commonly used in the treatment of chronic myeloproliferative diseases. Dermatological side effects are frequently seen in patients receiving longterm HU therapy. Cutaneous ulcers have been reported occasionally.We report on four patients with cutaneous ulcers whilst on long-term hydroxyurea therapy for myeloproliferative diseases. In all patients we were able to reduce the dose, or stop HU altogether and their ulcers markedly improved. Our observations suggest that cutaneous ulcers should be considered as possible side effect of long-term HU therapy and healing of the ulcers can be achieved not only by cessation of the HU treatment, but also by reducing the dose of hydroxyurea for a limited time.
Keywords: Hydroxyurea; ulcer; myeloproliferative disease; interferon